Tracking sinks of per- and polyfluoroalkyl substances in Florida soils: A community-informed study - Sanneri E. Santiago Borrés; Katherine Y. Deliz Quiñones; Ana Huynh; John A. Bowden; Jean C. Bonzongo; Antarpreet Jutla; Eric S. Coker (Elsevier, 2024)
Extensive use of per- and polyfluoroalkyl substances (PFAS) in various industrial and consumer products in the past has led to their widespread distribution in the environment. PFAS contamination has become a major environmental and public health threat worldwide, especially in communities impacted by industrial, commercial, and military activities. In 2021, twelve soil samples were collected from three distinct site types in Brevard County, Florida, based on community concerns: background sites, primary-source sites, and secondary-source sites. These sites comprised samples collected from both residential and industrial/commercial areas. Ultra-high performance liquid chromatography-tandem mass spectrometry was used to identify and quantify PFAS in the samples. The results show that PFAS were present in all soil samples, with the lowest and the highest concentrations being in background and primary sites, respectively. Total PFAS concentrations in both primary and secondary sites were generally one-order of magnitude greater than those reported in background sites. Perfluorooctanesulfonic acid concentrations were the most predominant among the 34 species of PFAS detected in the samples, with concentrations ranging from 0.04 to 2.63 ​ng/g. Analysis of variance of PFAS data reveals significant difference among study sites, with greater diversity and concentrations near primary sources followed by secondary sites and background sites. The results also demonstrate that long-chained PFAS are significantly more abundant in these soils than short-chained PFAS. Overall, our results should help prioritize future sampling locations for a rapid and systematic identification of PFAS in soils.